Syllabification nature in Bedouin-North Yemeni Arabic dialects (Bed-NYAD) - Alquhali, Sami A. M.; Gajendra, P.; Bajiri, Maryam E. S.; Ageed, Hussein Omer Ali Hussein (Linguistics and Culture Review, 2021)
This study is concerned with discussing the syllable structure or the syllable nature of the bedouin or nomadic north Yemeni Arabic dialect spoken mainly in five governorates namely, Aljawf, Tihamah, Amran, Sa’adah and Ma’rib, in Yemen referred to in the study as Bed-NYAD. The main goal of this paper is to show how many syllables are there in such dialects of the Yemeni Arabic and how they differ from those NYAD. Data collection was achieved with the help of a digital recorder. Many speakers of Bed-NYAD have been recorded for the sake of proving our claim that Bed-NYAD have different syllable nature from those other Yemeni dialects of Arabic. The finding of the study revealed that Bed-NYAD have five main types CV, CV:, CVC, CVCC and CV:C while NYAD have only three types of syllables CV, CVV, CVC and the semisyllable C.